La demanda laboral del Talento Humano especializado en el área administrativa de las compañías de la ciudad de Loja. - Sanmartín Sanmartín, Erika Yulissa (2023)
Currently, it is very important for companies to have specialized human talent in the administrative area, since this is the most important capital of the organization, therefore, it generates a great competitive advantage. In this sense, the main objective of this research is to analyze the labor demand for specialized human talent in the administrative area of companies in the city of Loja, making a comparison between micro, small, medium and large companies; the methodology used was based on a mixed approach, developing an exploratory-descriptive research; for its development, the survey and interview technique was applied, based on a questionnaire that helped to meet the objectives. The study population was 789 companies regulated by the Superintendence of Companies, obtaining a sample of 259 companies to be evaluated. As a result, it was obtained that in the companies of the city of Loja from the year 2019 to 2022 there were practically no job vacancies, instead, there was a large amount of unemployment, considering the pandemic that went through in the years 2020 and 2021, however, by 2022 the companies began to gradually return to their state prior to Covid-19, so that by 2023 it is estimated that the job vacancies will grow in relation to the business growth rate calculated based on the years 2014-2019. Likewise, the most required specialties in the different departments are professionals in Business Administration, Commercial Engineering, Human Resources Management, Finance, Accounting and Auditing Engineering and Marketing and Sales Management. In conclusion, the labor demand in the administrative area of companies in the city of Loja is minimal, even more so in small and micro companies, which hire personnel sporadically and only in operational areas.